Effects of 35% Carbamide Peroxide Gel on Surface Roughness and Hardness of Composite Resins - F. Sharafeddin; GR. Jamalipour (Tehran University of Medical Sciences, 2010)
Objective: Bleaching agents may not be safe for dental materials. The purpose of this invitro study was to evaluate the effects of Opalescent Quick "in-office bleaching gel" containing 35% carbamide peroxide on the surface roughness and hardness of microfilled (Heliomolar) and hybride (Spectrum TPH) composite resins. Materials and Methods: Twenty specimens of Spectrum TPH composite resins and twenty Heliomolar composite resins were fabricated using a metallic ring (6.5 mm diameter and 2.5 mm thickness) and light cured, then their surfaces were polished. Specimens of each composite resin were divided into two equal groups. Ten specimens of each type of composite were stored in water at 37°C as the control groups and 35% carbamide peroxide gel (Opalescence Quick) as the other group for 30 minutes a week for 3 weeks. Then the specimens were subject to roughness and hardness tests. Results: This study revealed that using 35% carbamide peroxide bleaching gels had no significant effect on the surface roughness of Spectrum TPH "hybrid" and Heliomolar "microfilled" composite resins. The surface hardness of Spectrum TPH composite treated with the subject gel significantly increased compared to heliomolar, which had no significant change after treatment with this bleaching gel. Conclusion: If tooth color matching of the composite had been satisfactory after office bleaching with 35% carbamide peroxide gel, this material would have been acceptable because it has no adverse effect on Heliomolar and Spectrum TPH composite resins.